Cycling specific postural stability during incremental exercise: The relationship with cyclists Functional Movement Screen score - Rannama, I.; Pedak, K.; Bazanov, B.; Port, K. (Journal of Human Sport & Exercise, 2017)
The purpose of this study was to characterise the changes in the power of the normalised ground reaction forces and COP swaying, as measures of the cycling stability and effectiveness of full body motion during an incremental cycling exercise; and to examine the relationships between cycling specific postural stability and cyclists ability to perform functional movements, measured by the FMS test.38 competitive road cyclists (19.2±2.3 yrs., 181.7±6.6 cm, 74.3±7.3 kg) performed Functional Movement Screen (FMS) test to evaluate their musculoskeletal state. Experimental cycling exercise was performed using the cyclist`s personal racing bikes mounted on the cycling ergometer Cyclus 2, which were fixed on two Kistler 9286B force plate. The 6 ground reaction force (GRF) components (3 linear and 3 angular), COP movement deviation and sway velocity were measured during incremental cycling exercise (step 2 min, increment 25W). Postural stability measures were calculated as power corrected standard deviations of COP and GRF components signals during 30 sec cycling in every incremental step. The paired t-test was used to control differences in postural stability measures between intensity levels and correlation analyses was used to evaluate relationships between postural stability and FMS scores. Results of the study indicate that most integrative cycling specific posture stability measure is COP sway velocity that is also most sensitive predictor of cyclist`s musculoskeletal state, measured by the FMS test. During an incremental cycling exercise the power normalised postural swaying decreased up to the intensity at the level of anaerobic threshold and during the level of the maximal aerobic power the postural stability decreased significantly.